Sie sind auf Seite 1von 9

For more such worksheets visit www.EduGain.com

(1)

A)
B)
C)
D)
E)

(2)

## ( -33 ) - 52 - 38 - 52 - 183 - ( -147 ) =

( -75 ) - ( -115 ) - ( -149 ) - 161 - 163 - ( -48 ) =
11 - 86 - 85 - ( -49 ) - ( -81 ) - 103 - 37 =
( -10 ) - ( -140 ) - ( -115 ) - 11 - 64 - ( -46 ) - 198 =

A)
B)
C)
D)
E)

(3)

## 165 + ( -122 ) + ( -176 ) + ( -35 ) + ( -184 ) + ( -193 ) + 18 =

73 + ( -55 ) + 105 + ( -107 ) + 66 + ( -144 ) + 194 + ( -123 ) =
142 + ( -92 ) + ( -138 ) + ( -20 ) + ( -136 ) + 148 + 171 + ( -75 ) + ( -167 ) =
195 + ( -111 ) + ( -21 ) + ( -38 ) + ( -86 ) + 144 + ( -14 ) =
182 + ( -108 ) + ( -103 ) + 14 + 127 + ( -199 ) + ( -81 ) + ( -181 ) =

A)
B)
C)
D)
E)

## 3373 and -1231 from -9342 =

7217 and -4096 from 4540 =
-1378 and -998 from -6447 =
1861 and -3608 from -7942 =
8118 and -1947 from 1125 =

## Many more such worksheets can be

generated at www.EduGain.com

## Personal use only, commercial use is strictly prohibitated

(1)

A)

39
Step 1
The given expression can be expressed as:
3 - ( -131 ) - ( -14 ) - 109
= 3 + 131 + 14 - 109
= 39
Step 2
Therefore the value of expression 3 - ( -131 ) - ( -14 ) - 109 is 39.

B)

-211
Step 1
The given expression can be expressed as:
( -33 ) - 52 - 38 - 52 - 183 - ( -147 )
= -33 - 52 - 38 - 52 - 183 + 147
= -211
Step 2
Therefore the value of expression ( -33 ) - 52 - 38 - 52 - 183 - ( -147 ) is -211.

C)

-87
Step 1
The given expression can be expressed as:
( -75 ) - ( -115 ) - ( -149 ) - 161 - 163 - ( -48 )
= -75 + 115 + 149 - 161 - 163 + 48
= -87
Step 2
Therefore the value of expression ( -75 ) - ( -115 ) - ( -149 ) - 161 - 163 - ( -48 ) is -87.

D)

-170
Step 1
The given expression can be expressed as:
11 - 86 - 85 - ( -49 ) - ( -81 ) - 103 - 37
= 11 - 86 - 85 + 49 + 81 - 103 - 37
= -170
Step 2
Therefore the value of expression 11 - 86 - 85 - ( -49 ) - ( -81 ) - 103 - 37 is -170.

## Personal use only, commercial use is strictly prohibitated

E)

18
Step 1
The given expression can be expressed as:
( -10 ) - ( -140 ) - ( -115 ) - 11 - 64 - ( -46 ) - 198
= -10 + 140 + 115 - 11 - 64 + 46 - 198
= 18
Step 2
Therefore the value of expression ( -10 ) - ( -140 ) - ( -115 ) - 11 - 64 - ( -46 ) - 198 is
18.

## Personal use only, commercial use is strictly prohibitated

(2)

A)

-570
Step 1
The value of 165 + ( -122 ) + ( -176 ) + ( -35 ) + ( -184 ) + ( -193 ) + 18 can be found by
the following steps:
Step 2
Separating positive and negative terms like as:
165 + 18 + ( -122 -176 -35 -184 -193 )
Step 3
Adding positive and negative terms separately.
183 + ( -710 )
Step 4
Subtracting the sum of negative terms from the positive terms.
183 -710 = -570.
Step 5
Therefore the value of 165 + ( -122 ) + ( -176 ) + ( -35 ) + ( -184 ) + ( -193 ) + 18 is 570.

B)

-9
Step 1
The value of 73 + ( -55 ) + 105 + ( -107 ) + 66 + ( -144 ) + 194 + ( -123 ) can be found
by the following steps:
Step 2
Separating positive and negative terms like as:
73 + 105 + 66 + 194 + ( -55 -107 -144 -123 )
Step 3
Adding positive and negative terms separately.
438 + ( -429 )
Step 4
Subtracting the sum of negative terms from the positive terms.
438 -429 = -9.
Step 5
Therefore the value of 73 + ( -55 ) + 105 + ( -107 ) + 66 + ( -144 ) + 194 + ( -123 ) is -9.

C)

-217
Step 1
The value of 142 + ( -92 ) + ( -138 ) + ( -20 ) + ( -136 ) + 148 + 171 + ( -75 ) + ( -167 )
can be found by the following steps:

## Personal use only, commercial use is strictly prohibitated

Step 2
Separating positive and negative terms like as:
142 + 148 + 171 + ( -92 -138 -20 -136 -75 -167 )
Step 3
Adding positive and negative terms separately.
461 + ( -628 )
Step 4
Subtracting the sum of negative terms from the positive terms.
461 -628 = -217.
Step 5
Therefore the value of 142 + ( -92 ) + ( -138 ) + ( -20 ) + ( -136 ) + 148 + 171 + ( -75 ) +
( -167 ) is -217.
D)

-15
Step 1
The value of 195 + ( -111 ) + ( -21 ) + ( -38 ) + ( -86 ) + 144 + ( -14 ) can be found by
the following steps:
Step 2
Separating positive and negative terms like as:
195 + 144 + ( -111 -21 -38 -86 -14 )
Step 3
Adding positive and negative terms separately.
339 + ( -270 )
Step 4
Subtracting the sum of negative terms from the positive terms.
339 -270 = -15.
Step 5
Therefore the value of 195 + ( -111 ) + ( -21 ) + ( -38 ) + ( -86 ) + 144 + ( -14 ) is -15.

E)

-423
Step 1
The value of 182 + ( -108 ) + ( -103 ) + 14 + 127 + ( -199 ) + ( -81 ) + ( -181 ) can be
found by the following steps:
Step 2
Separating positive and negative terms like as:
182 + 14 + 127 + ( -108 -103 -199 -81 -181 )
Step 3
Adding positive and negative terms separately.

## Personal use only, commercial use is strictly prohibitated

323 + ( -672 )
Step 4
Subtracting the sum of negative terms from the positive terms.
323 -672 = -423.
Step 5
Therefore the value of 182 + ( -108 ) + ( -103 ) + 14 + 127 + ( -199 ) + ( -81 ) + ( -181 )
is -423.

## Personal use only, commercial use is strictly prohibitated

(3)

A)

-11484
Step 1
The sum of 3373 and -1231
3373 + (-1231) = 3373 -1231 = 2142
Step 2
Now subtract 2142 from -9342
-9342 - 2142 = -11484
Step 3

B)

1419
Step 1
The sum of 7217 and -4096
7217 + (-4096) = 7217 -4096 = 3121
Step 2
Now subtract 3121 from 4540
4540 - 3121 = 1419
Step 3

C)

-4071
Step 1
The sum of -1378 and -998
-1378 + (-998) = -1378 -998 = -2376
Step 2
Now subtract (-2376) from -6447
-6447 - (-2376) = -6447 + 2376 = -4071
Step 3

D)

-6195
Step 1
The sum of 1861 and -3608
1861 + (-3608) = 1861 -3608 = -1747
Step 2

## Now subtract (-1747) from -7942

-7942 - (-1747) = -7942 + 1747 = -6195
Step 3
E)

-5046
Step 1
The sum of 8118 and -1947
8118 + (-1947) = 8118 -1947 = 6171
Step 2
Now subtract 6171 from 1125
1125 - 6171 = -5046
Step 3